Role of 1,25-Dihydroxyvitamin D3 on Osteogenic Differentiation and Mineralization of Chicken Mesenchymal Stem Cells - Chen, Chongxiao; Adhikari, Roshan; White, Dima Lynn; Kim, Woo Kyun (Frontiers in Physiology, 2021)
1,25-dihydroxyvitamin D3 (1,25OHD) has been suggested to play an important role in osteogenic differentiation and mineralization. However, limited data have been reported in avian species. In the present study, the direct role of 1,25OHD on osteogenic differentiation and mineralization in chicken mesenchymal stem cells (cMSCs) derived from day-old broiler bones was investigated. cMSCs were treated with control media (C), osteogenesis media (OM), OM with 1, 5, 10 and 50 nM 1,25OHD, respectively. The mRNA samples were obtained at 24 h, 48 h, 3 d, and 7 d to examine mRNA expression of key osteogenic genes (RUNX2, BMP2, COL1A2, BGLAP, SPP1, and ALP). Cells were stained at 7, 14 and 21 d using Von Kossa (mineralization), Alizarin Red (mineralization) and Alkaline Phosphatase (early marker) staining methods. From the mRNA expression results, we found a time-dependent manner of 1,25OHD on osteoblast differentiation and mineralization. In general, it showed an inhibitory effect on differentiation and mineralization during the early stage (24 h and 48 h), and a stimulatory effect during the late cell stage (3 d and 7 d). The staining showed 1,25OHD had an inhibitory effect on ALP enzyme activities and mineralization in a dosage-dependent manner up to 14 d. However, at 21 d, there was no difference between the treatments. This study provides a novel understanding of the effects of 1,25OHD on osteogenic differentiation and mineralization of cMSCs depending on cell stage and maturity.